KITAB JAWI DAN KARYA SAINS: WACANA KETAMADUNAN DAN JATI DIRI ORANG MELAYU - Sulaiman, Abdullah; al-Edrus, Syed Muhammad Dawilah (Journal of Techno-Social, 2012)
Kitab Jawi and the Malay Archipelago is a topic which is synonymous with the question of identity and civilization of the Malay community. Thus it has managed to assimilate the strength and empowering excellence of the Malay ummah as early as the 14th century when Ibn Battuta, a traveler from Morocco mentioned in his memoirs entitled ' al - Rihlah ' 1345M that he had stopped at Pasai under the reign of Sultan Malik al – Zahir, a pious and righteous sultan who hold strongly to the Shafi'i madhhab. The Islamic scholars played their roles to disseminate the religion of Islam to the local communities making the Kitab Jawi as the main vehicle. The role of the Kitab Jawi is not only related to the religious aspects but included science and technology. As an example, mathematics ans astronomy in Islam are closely related to the content in al-Qur’an. Among the Malay scholars who were expert in this field were Syeikh Ahmad al-Fathani, Syeikh Tahir Jalaluddin and Syeikh Ahmad al- Minangkabau.